Hollow ZnO Nanospheres Enhance Anticancer Immunity by Promoting CD4+ and CD8+ T Cell Populations In Vivo. Issue 38 (21st August 2017) - Wang, Xiupeng; Li, Xia; Ito, Atsuo; Sogo, Yu; Watanabe, Yohei; Tsuji, Noriko M.
Abstract : Appropriate adjuvant aiding in generating robust anticancer immunity is crucial for cancer immunotherapy. Herein, hollow ZnO (HZnO) nanospheres are synthesized by a facile method using carbon nanospheres as the template. The HZnO nanospheres significantly promote the cellular uptake of a model antigen, and cytokine secretion by antigen‐presenting cells in vitro. HZnO loaded with ovalbumin and polyinosinic‐polycytidylic acid (poly(I:C)) inhibits cancer growth and metastasis to inguinal lymph node in a cancer cell challenge model. Moreover, HZnO loaded with autologous cancer antigens inhibits cancer cell growth in a cancer cell re‐challenge model. HZnO nanospheres significantly improve the CD4 + and/or CD8 + T cell population in splenocytes of mice in both cancer cell challenge model and re‐challenge model. The HZnO nanospheres can be used for cancer immunotherapy as adjuvant. Abstract : Hollow ZnO nanospheres significantly promote the cellular uptake of a model cancer antigen, increase the CD4 + and/or CD8 + T cell populations in splenocytes of mice, and improve anticancer immunity. Hollow ZnO nanospheres are promising as an adjuvant for cancer immununotherapy.